PERENCANAAN STRUKTUR GEDUNG HOTEL 5 LANTAI DI DAERAH PANGANDARAN JAWA BARAT MENGGUNAKAN PROGRAM SAP 2000 - Fatmawati Oemar; Trah Nugroho (FTSP Universitas Jayabaya, 2019)
Pangandaran is one of the districts in West Java Province that has a big amount of citizen growth and also various nature potential. Thus, the local Government needs to focus on the development of the district, whether it is a village housing or hotel for tourists. This analysis is aimed to design and calculate a strong and durable construction structure of Hotel Building near to the beach which has strong wind loads and also earthquake/seismic loads. Through this analysis, will be designed a structure by modeling in SAP 2000 program to help to define materials and loads that will be used in this analysis, where the configuration of rebar is the output. The first step is designing the plan and the specification of materials, soil properties, and also component of structure. Then, making a model in SAP 2000 and inputting the working loads to each component of the structure. After getting the value of moments(M), shear (V) and normal (N) loads, calculating regarding the valid standard is the next step. As the result, this analysis shows that the well planned and designed structure is needed in designing and building. With the most concrete rebar ratio are under 0,0025, it is concluded that the reinforced status of the beams are under-reinforced. For column, the ultimate moment value is below the nominal moment multiplied by strength reduction factor. And the slab, the value of rebar ratio is below minimum rebar ratio. Eventually, all types of the slab use the value of minimum rebar ratio.